Dysmenorrhea in adolescents and young adults: a review in different country - De Sanctis, Vincenzo; Soliman, Ashraf T; Elsedfy, Heba; Soliman, Nada A; Soliman, Rania; El Kholy, Mohamed (Acta Biomedica Atenei Parmensis, 2017)
Background: Dysmenorrhea is still an important public health problem which may have a negative impact on female health, social relationships, school or work activities and psychological status. Methods: The aim of this review is a better understanding of the epidemiology of dysmenorrhoea and its effect on public health. Published studies in English providing relevant information on dysmenorrhea were identified by searching PubMed, Embase and Google; restricting the population to adolescents and young adult women and the year of publishing from 2010 to August 2015, based on the keywords ‘dysmenorrhea’, ‘adolescents’ and ‘epidemiology’. In addition, the reference lists of the selected articles were examined. Results: We found 50 studies that met our inclusion criteria. The majority were cross-sectional studies on 41,140 adolescents and young women published from 2010 onward. The prevalence of dysmenorrhea varied from 34 % (Egypt) to 94% (Oman) and the number of participants, reporting very severe pain varied from 0.9 % (Korea) to 59.8% (Bangladesh). Adolescents who missed school due to dysmenorrhoea ranged from 7.7% to 57.8% and 21.5% missed social activities. About 50% of students (53.7%-47.4%) reported a family history of dysmenorrhea. Incidence of dysmenorrhea was 0.97 times lower as age in-creased (p <0.006). Despite the high prevalence of dysmenorrhea in adolescents, many girls did not receive professional help or treatment. Mothers were the most important persons the girls turned to for answers regarding menstruation, followed by peers (52.9%) and school nurse. From 21% to 96% practised self–medication either by pharmacological or non pharmacological interventions. The limitation of these studies was that they did not distinguish between primary dysmenorrhea and secondary dysmenorrhea. Conclusions: The main gynecological complaint of adolescents is dysmenorrhea. Morbidity due to dysmenorrhea represents a substantial public health burden. It is one of the leading causes of absenteeism from school and work and is responsible for significant diminished quality of life. Despite its high prevalence and associated negative effects, many adolescents do not seek medical care for this condition. Appropriate counselling and management should be instituted among female students to help them cope with the challenges of dysmenorrhea. Information, education and support should also be extended to parents, school peer leaders, and hostel administrators in order to address the reproductive health needs of the female students